Serial mediation effects of reflective practice and creative expression on artistic skills development: a cross-cultural analysis in university art education - Li, Mengdie; Vasilyevna, Alekseeva Galina (Frontiers in Psychology, 2025)
IntroductionNumerous research efforts have explored the antecedents of artistic skills development among painting students. However, the role of cultural exposure in fostering this development has been largely overlooked. The study aims to address this gap by examining cultural exposure as a prelude to artistic skills development. The study also explores the intermediary pathways through which cultural exposure might stimulate artistic skills development.MethodsWe employed the experiential learning theory to conceptualize the proposed model and collected data from 300 painting majors using a stratified random sampling technique to ensure cultural diversity. Using the Structural Equation Modeling technique, we analyzed the measurement and structural models.ResultsResults indicate that cultural exposure is significantly linked to artistic skills development. Furthermore, reflective practice and creative expression significantly mediate this phenomenon. The study also finds significant serial mediation effects of cultural exposure on reflective practice and then creative expression, leading to enhanced artistic skills development.DiscussionOur findings offer substantial policy implications that emphasize the need for curricula to encapsulate both cultural immersion and self-reflection practices as a mean to foster artistic skills development in university art education.